Role for Atlantic inflows and sea ice loss on shifting phytoplankton blooms in the Barents Sea. Issue 6 (26th June 2017) - Oziel, L.; Neukermans, G.; Ardyna, M.; Lancelot, C.; Tison, J‐L.; Wassmann, P.; Sirven, J.; Ruiz‐Pino, D.; Gascard, J‐C.
Abstract: Phytoplankton blooms in the Barents Sea are highly sensitive to seasonal and interannual changes in sea ice extent, water mass distribution, and oceanic fronts. With the ongoing increase of Atlantic Water inflows, we expect an impact on these blooms. Here, we use a state‐of‐the‐art collection of in situ hydrogeochemical data for the period 1998–2014, which includes ocean color satellite‐derived proxies for the biomass of calcifying and noncalcifying phytoplankton. Over the last 17 years, sea ice extent anomalies were evidenced having direct consequences for the spatial extent of spring blooms in the Barents Sea. In years of minimal sea ice extent, two spatially distinct blooms were clearly observed: one along the ice edge and another in ice‐free water. These blooms are thought to be triggered by different stratification mechanisms: heating of the surface layers in ice‐free waters and melting of the sea ice along the ice edge. In years of maximal sea ice extent, no such spatial delimitation was observed. The spring bloom generally ended in June when nutrients in the surface layer were depleted. This was followed by a stratified and oligotrophic summer period. A coccolithophore bloom generally developed in August, but was confined only to Atlantic Waters. In these same waters, a late summer bloom of noncalcifying algae was observed in September, triggered by enhanced mixing, which replenishes surface waters with nutrients. Altogether, the 17 year time‐series revealed a northward and eastward shift of the spring and summer phytoplankton blooms. Key Points: A 17 year time‐series of remotely sensed and in situ observations is used to describe the variability of phytoplankton blooms At least three distinct blooms were revealed and are partly controlled by the position of the sea ice edge and the polar front A north‐eastward shift of the spring and summer blooms was observed